Sound Communication in Fishes - Ladich, Friedrich (Animal Signals and Communication,, 2015)
This volume examines fish sounds that have a proven signal function, as well as sounds assumed to have evolved for communication purposes. It provides an overview of the mechanisms, evolution and neurobiology behind sound production in fishes, and discusses the role of fish sounds in behavior with a special focus on choice of mate, sex-specific and age-specific signaling. Furthermore, it highlights the ontogenetic development of sound communication and ecoacoustical conditions in fish habitats and the influence of hormones on vocal production and sound detection. Sound Communication in Fishes offers a must-have compendium for lecturers, researchers and students working in the fields of animal communication, fish biology, neurobiology and animal behavior.